2012
DOI: 10.1371/journal.pone.0046245
|View full text |Cite
|
Sign up to set email alerts
|

Free Cholesterol Induces Higher β-Sheet Content in Aβ Peptide Oligomers by Aromatic Interaction with Phe19

Abstract: Accumulating experimental evidence support an enhancing effect of free cholesterol on amyloid-beta (Aβ) aggregation. To probe the mechanisms of cholesterol-mediated Aβ aggregation, we applied all-atom molecular dynamic simulations on Aβ42 peptides in presence of free cholesterol. Several control systems were also designed to examine the specificity of cholesterol-residue interactions, including mutation on aromatic residue, substitution of cholesterol with sphingomyelin (SM) and DPPC bilayer, and a mixing SM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…This is similar to that of the unmodified cholesterol and DC-cholesterol, suggesting that the negatively charged sulfate moiety of cholesterol-SO 4 does not dramatically influence its function in mediating Aβ aggregation. Taken together, if non-aggregating cholesterol and the derivatives modify the aggregation of Aβ via binding with the peptide, as suggested by recent simulation studies, 30, 32 they presumably interact with Aβ peptides mainly through hydrophobic interactions. The positively or negatively charged groups in the cholesterol derivatives studied here likely are not involved in critical interactions in this process.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…This is similar to that of the unmodified cholesterol and DC-cholesterol, suggesting that the negatively charged sulfate moiety of cholesterol-SO 4 does not dramatically influence its function in mediating Aβ aggregation. Taken together, if non-aggregating cholesterol and the derivatives modify the aggregation of Aβ via binding with the peptide, as suggested by recent simulation studies, 30, 32 they presumably interact with Aβ peptides mainly through hydrophobic interactions. The positively or negatively charged groups in the cholesterol derivatives studied here likely are not involved in critical interactions in this process.…”
Section: Resultsmentioning
confidence: 73%
“…32 Using all-atom molecular dynamic simulations, Zhou et al reported an important role of steroid-benzyl interaction in cholesterol-mediated aggregation. 30 More specifically, the amino acid Phe19 was found to be critical for this interaction. Our experimental results are in accord with these simulation results.…”
Section: Resultsmentioning
confidence: 97%
“…[24][25][26][27][28][29] Simulation of aggregation and release processes 26,30,31 are particularly relevant to the work presented here because they can compete with unfolding, penetration, and binding phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Both computer simulations and complementary experiments such as NMR and single-molecule imaging and spectroscopy are urgently needed to uncover the basic mechanisms governing these events [28]. There have been a number of recent MD simulations of Aβ peptide in or on model membranes with different starting structures [13, 14, 2933]. Simulations of aggregation and release processes [30, 31, 33] of Aβ are relevant to this work, because they represent the future molecular events that take place after the completion of the predicted protein orientational transitions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of recent MD simulations of Aβ peptide in or on model membranes with different starting structures [13, 14, 2933]. Simulations of aggregation and release processes [30, 31, 33] of Aβ are relevant to this work, because they represent the future molecular events that take place after the completion of the predicted protein orientational transitions. In addition, our predicted structures of the new protein orientational states may signal further downstream folding/unfolding, binding and self-aggregation phenomena in the complex membrane-associated amyloid cascade pathways that may contribute to the pathogenesis of Alzheimer’s.…”
Section: Introductionmentioning
confidence: 99%